Relative health performance in BRICS over the past 20 years: the winners and losers - Dennis Petrie; Kam Ki Tang (The World Health Organization, 2014)
Objective To determine whether the health performance of Brazil, the Russian Federation, India, China and South Africa - the countries known as BRICS - has kept in step with their economic development. Methods Reductions in age- and sex-specific mortality seen in each BRICS country between 1990 and 2011 were measured. These results were compared with those of the best-performing countries in the world and the best-performing countries with similar income levels. We estimated each country's progress in reducing mortality and compared changes in that country's mortality rates against other countries with similar mean incomes to examine changes in avoidable mortality. Findings The relative health performance of the five study countries differed markedly over the study period. Brazil demonstrated fairly even improvement in relative health performance across the different age and sex subgroups that we assessed. India's improvement was more modest and more varied across the subgroups. South Africa and the Russian Federation exhibited large declines in health performance as well as large sex-specific inequalities in health. Although China's levels of avoidable mortality decreased in absolute terms, the level of improvement appeared low in the context of China's economic growth. Conclusion When evaluating a country's health performance in terms of avoidable mortality, it is useful to compare that performance against the performance of other countries. Such comparison allows any country-specific improvements to be distinguished from general global improvements.